2003
DOI: 10.1016/s1044-0305(03)00127-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of oxidation products and free radicals of tryptophan by mass spectrometry

Abstract: New oxidation products and free radicals derived from tryptophan (Trp) oxidation under Fenton reaction conditions were identified using mass spectrometry. After the oxidation of tryptophan using hydrogen peroxide and iron (II) system (Fenton reaction), mono-and dihydoxy tryptophans and N-formylkynurenine were identified using electrospray mass spectrometry (ES-MS) and ES-MS/MS. Besides these products, new products resulting from the reaction of tryptophan and oxidized tryptophan and 3-methyl indole derivatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 30 publications
10
68
0
Order By: Relevance
“…Along the same line, DMPO/CBQ-OH adduct may exist in 2 of the 3 possible redox forms: the DMPO/CBQ-OH nitroxide form and its corresponding nitrone form as shown in Scheme 3. Several previous studies showed that DMPO radical adducts were detected by MS in one or all of the 3 different forms (12)(13)(14)(15). Under our HPLC/ESI-MS experimental conditions and based on the FTICR high resolution MS data, the measured molecule ion peak at m/z 268.0383 could be assigned to the oxidized nitrone form (theoretical mass 268.0377) of the DMPO/CBQ-OH nitroxide radical adduct.…”
Section: Formation Of Cbq(oh)-o-t-bu Wasmentioning
confidence: 61%
“…Along the same line, DMPO/CBQ-OH adduct may exist in 2 of the 3 possible redox forms: the DMPO/CBQ-OH nitroxide form and its corresponding nitrone form as shown in Scheme 3. Several previous studies showed that DMPO radical adducts were detected by MS in one or all of the 3 different forms (12)(13)(14)(15). Under our HPLC/ESI-MS experimental conditions and based on the FTICR high resolution MS data, the measured molecule ion peak at m/z 268.0383 could be assigned to the oxidized nitrone form (theoretical mass 268.0377) of the DMPO/CBQ-OH nitroxide radical adduct.…”
Section: Formation Of Cbq(oh)-o-t-bu Wasmentioning
confidence: 61%
“…Mass spectrometry (MS) has been shown to be a suitable tool to identify and verify spin adducts. these techniques were applied to the characterization of radical adducts of the nitrones benzylidene(tert-butyl)azane oxide (PBN) 15,16 , 4-{[tertbutyl(oxido)imino]-methyl} pyridine 1-oxide (PoBN), [17][18][19][20] 2,2 dimethyl-3,4-dihydropyrroline N-oxide (DMPo), [21][22][23][24][25][26][27] N-arylc,c-dimethoxycarbonylnitrones 28 and (2-methyl-1-oxido-3,4-dihydro-2H-pyrrol-2-yl) phosphonate (DEPMPo). 29 the mass spectrometric analyses were performed on the isolated radical spin adducts using high-performance liquid chromatography (HPLc) or with on-line chromatographic system such as HPLc or Gc.…”
Section: Europeanmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] recently, the structural determination of free radical spin adducts from a complex mixture has been reported without any preliminary separation. [22][23][24][25][26][27][28][29] Each method presents different advantages and disadvantages. Isolation with chromatographic systems is a long procedure and does not permit the analysis of the initial paramagnetic spin adducts.…”
Section: Europeanmentioning
confidence: 99%
“…However, to quantify the individual oxidation products, the development of more advanced technology is awaited [25]. The data presented here suggest that the antiserum recognizes NFK on an oxidized protein as well as kynurenine-bound proteins.…”
Section: Discussionmentioning
confidence: 93%